The First Record of Fusarium incarnatum as Wilting Agent on Tomato Plants in Iraq - Al- Masoudi, Rasha Khalid Hussein; Neamat J. AL Judy, (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
Fusarium wilt is one of the most significant diseases that affects tomato plants and is caused by the fungus Fusarium oxysporum, whether in fields or greenhouses. The current research aimed to identify the Fusarium incarnatum (Desm.) Sacc. agent that causes Fusarium wilt on tomato plants for the first time in Iraq by morphological and molecular methods, in addition to detecting the phylogenetic distance and similarity of the Iraqi isolates to other isolates globally. In January of 2023, the wilt signs were apparent on wilted tomato plants in Al-Mahmoudiya fields in Iraq. The isolate was confirmed and molecularly diagnosed according to the internal transcribed spacer (ITS) region. The sequences of ITS region for the isolate have been presented to the database in the NCBI Gen Bank for the first time, and it obtained their accession number (OQ439282.1). F.incarantum was isolated and purified and identified by using morphological and microscopic features, the morphological features of F.incarnatum isolate were observed on PDA media and under a microscope revealed that macroconidia have curved shapes, three to five septate, and basal cells with a foot shape. The pathogenicity of the fungus F.incarnatum showed the fungus's ability to cause wilting disease in healthy tomato plants at 90.33%, this demonstrates that the Fusarium isolate can create strains that can attack the host continually. Additionally, the phylogenetic tree revealed the genetic relationship between the Iraq isolate and other global isolates and it showed the Iraq isolate (OQ439282.1) is in the same clade as the Turkey isolate, India isolates, and China isolate with similarity 100%, and this clade shares 99.60% similarity with another clade, including Thailand, Taiwan, Nigeria, South Korea, Pakistan, Japan, Egypt, USA, and Tunisia isolates. As far as we are aware, this is the first morphological and molecular recording of F.incarantum on an Iraqi tomato plants